The relationship between a combination of vitamin D deficiency and hyperuricemia and the severity of coronary artery disease in myocardial infarction patients - Mustafa Umut Somuncu; Nail Güven Serbest; Ferit Akgül; Mustafa Ozan Çakır; Tunahan Akgün; Fatih Pasa Tatar; Murat Can; Abdulkadir Tekin (KARE Publishing, 2020)
Objective: Vitamin D deficiency has been shown to be associated with coronary artery disease (CAD). In addition, there are studies suggesting that hyperuricemia is an independent risk factor for atherosclerosis, whereas the relationship between the combination of these 2 parameters and severity of CAD remains unclear. The aim of this study was to investigate the association between the combination of vitamin D deficiency and hyperuricemia and the extent of CAD. Methods: A total of 502 patients who had experienced myocardial infarction (MI) were included in this cross-sectional study. The 25-hydroxyvitamin D (25OHD) and serum uric acid (SUA) levels were measured in blood samples taken at the time of admission. A 2x2 factorial design was used to create groups according to the presence of hyperuricemia (>7 mg/dL) and vitamin D deficiency (<20 ng/mL). All of the patients underwent coronary angiography and the severity of CAD was determined using the Gensini score, SYNTAX score, and the number of diseased vessels. Results: Both vitamin D deficiency and hyperuricemia were present in 83 patients (16.5%). Patients with hyperuricemia/vitamin D deficiency had more multivessel disease (24.1% vs 8.5%), and a higher SYNTAX score and Gensini score compared with the control group (13.9+-8.0 vs. 9.5+-6.3, 54.8+-24.0 vs. 40.5+-19.9, respectively). Age, male sex, presence of diabetes mellitus, family history of CAD, and levels of SUA and 25OHD were independent predictors of the severity of CAD. Moreover, the hyperuricemia/vitamin D deficiency group had 4 times greater odds of severe CAD than the control group. Conclusion: The combination of hyperuricemia and vitamin D deficiency appears to be an independent predictor of severe CAD in MI patients.